THE EFFECT OF SMOKING ON ANASTOMOTIC STRICTURE RATES FOLLOWING OESOPHAGECTOMY. (8th June 2013) - Burnside, N; Beattie, R; Gambardella, I; McManus, K G
Abstract : Introduction: Anastomotic stricture following oesophagectomy causes a significant morbidity and often necessitates repeated dilation or even revision surgery. Smoking has been identified as a cause of microvascular disease associated with ischaemia. Aims/Background: Previously identified as an independent cause of anastomotic stricture following colorectal surgery, this study assessed the effects of smoking on stricture rates following all stomach-to-neck type oesophagectomies in oesophageal cancer patients. Method: 66 sequential patients had oesophagectomy for oesophageal cancers by a single surgeon. Multiple cancer types were included in the analysis. All medical records were reviewed and a multivariate analysis was carried out to identify risk factors. Patients were divided into current smokers, smoking within six weeks of the surgery, ex-smokers, those with a significant smoking history, and non-smokers. Results: The rate of anastomotic strictures in current smokers was 52% (11 of 21 patients), in ex-smokers was 9% (4 of 44 patients), and in patients who had never smoked was 0% (0 of 1 patients). The data was analysed and the difference stricture rates in current smokers and ex-smokers was found to be statistically significant (p-value 0.0002). Conclusion: Active smoking within six weeks of surgery is an independent extremely significant risk factor for anastomotic strictures following stomach to neck oesophagectomy.